Survivable optical network topology - Al-Waeli, Wafaa Abood Rawdhan (2020)
The demand for increased bandwidth is on the rise given the increased need for data consumption to meet the present and future requirements for information and communication technology (ICT) deployments. Thus, requiring high capacity optical links to support this expansion. Optical networks offer high-capacity fiber links for the ICT access networks, but comes with survivability concerns. The aim of this research is to assess the best approach for improving the survivability of an optical network via topology augmentation. Networks must provide reliable important services, and these networks continuously grow to cater for the ever-increasing number of clients. To improve the availability of optical networks, this project proposed to increase the network topology by adding a link(s) of appropriate length between nodes to eliminate the problem of "trap topology" so that the failure of any link with other links can be compensated. The Suurballe’s algorithm was coded in MATLAB so that we obtained the best probability for the network by finding multiple separate paths. The most important advantages of the method used is its speed in calculating availability and its effectiveness in finding the alternate line between stations in the event of a sudden cut. An optical network consisting of stations and paths is designed for the purpose of invoking them in the MATLAB simulation program and and test their paths in case the network is exposed to the most difficult conditions. The method used to develop the network, as well as the Suurballe’s algorithm, contributed to raising the survivability rate to three time than the first topology design and reduce the restoration time to a minimum a less as possible. It is believed that this method can be very useful in providing optical fiber networks. The continued survivability of optical fiber networks preserves customer data from loss and helps in increasing customer numbers continuously.